2005
DOI: 10.1002/jcb.20480
|View full text |Cite
|
Sign up to set email alerts
|

Angiostatin's molecular mechanism: Aspects of specificity and regulation elucidated

Abstract: Tumor growth requires the development of new vessels that sprout from pre-existing normal vessels in a process known as ''angiogenesis'' [Folkman (1971) N Engl J Med 285:1182-1186. These new vessels arise from local capillaries, arteries, and veins in response to the release of soluble growth factors from the tumor mass, enabling these tumors to grow beyond the diffusion-limited size of approximately 2 mm diameter. Angiostatin, a naturally occurring inhibitor of angiogenesis, was discovered based on its abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0
8

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 115 publications
3
75
0
8
Order By: Relevance
“…10 Angiostatin is derived from degradation of plasminogen by proteases such as cathepsin D and MMPs, resulting in a molecule comprised of kringle domains 1 through 4. 81,82 Studies in mice indicate that angiostatin inhibits glioma angiogenesis and growth 83,84 through binding of ␣ v ␤ 3 on proliferating endothelial cells, result in apoptosis. 81,85 NG2 chondroitin sulfate proteoglycan made by tumor-associated pericytes acts in a pro-angiogenic manner by sequestering angiostatin and decreasing its bioactivity.…”
Section: Anti-angiogenic Factorsmentioning
confidence: 99%
“…10 Angiostatin is derived from degradation of plasminogen by proteases such as cathepsin D and MMPs, resulting in a molecule comprised of kringle domains 1 through 4. 81,82 Studies in mice indicate that angiostatin inhibits glioma angiogenesis and growth 83,84 through binding of ␣ v ␤ 3 on proliferating endothelial cells, result in apoptosis. 81,85 NG2 chondroitin sulfate proteoglycan made by tumor-associated pericytes acts in a pro-angiogenic manner by sequestering angiostatin and decreasing its bioactivity.…”
Section: Anti-angiogenic Factorsmentioning
confidence: 99%
“…17) Since our results showed that ANXA2 expression was downregulated by HT1080-CM but upregulated by VEGF, HT1080-CM treatment may cause a response similar to prostate cancer. ANXA2 is also a cell surface receptor for angiostatin, which is a potent endoge- 19,20) It is possible that the downregulation of ANXA2 expression by HT1080-CM promotes CM-induced angiogenesis through the suppression of the effect of angiostatin.…”
Section: )mentioning
confidence: 99%
“…However, some of these enzymes can also, in defined circumstances, inhibit angiogenesis. Angiostatin, a potent inhibitor of angiogenesis, is a proteolytic fragment of plasminogen [10,11] and matrix metalloproteinases can generate anti-angiogenic fragments by proteolytic processing of some ECM proteins (see above, and [12]). As another example, two metalloproteinases of the ADAMTS family, ADAMTS-1 and -8, were also reported to strongly inhibit angiogenesis [13,14].…”
Section: Introductionmentioning
confidence: 99%